Extratos vegetais : efeitos sobre o desenvolvimento in vitro do fungo simbionte e na longevidade de operárias de Atta sexdens (Hymenoptera: Formicidae) - Souza, Marcelo Dias de (2012)
The objective this study was analyze the effects of different plant extracts on workers of Atta sexdens by powering supplied in diet and in the in vitro development of symbiotic fungus Leucoagaricus gongylophorus in different concentrations. The experiment was conducted in the Pathology Forest Laboratory of college of Forestry (FENF) Federal University of Mato Grosso (UFMT). The fungus and the ants were collected from nests presents in the campus of Cuiabá. The fungus was inoculated in the media PDA added with the plant extracts in different proportions, in dishes Petri. The dishes were kept in climatic chambers of type BOD at temperature of 25 ± 1 °C in the dark, for a period of 42 days. The fungal growth was measured weekly by the diameter of the colony. The ants were placed in Petri dishes (100mm x 15mm) and maintained in a climatic room at 26 ± 1°C, being the dishes lined with filter paper, containing ten ants/dishes in which the ants were maintained with artificial diets containing plant extracts and, which was checked every 24 hours the number of dead ants per dishes. The symbiotic fungus has a differently growth in relation to the extracts provided in the dishes, being the media added with the extracts of Physocalymma scaberrimum, Amburana acreana, Cedrela fissilis, Magonia pubescens, Leucaena leucocephala and Swietenia macrophylla inhibit the fungal growth, even at low concentrations. The leafcutter ants may survive for up to nine days without the presence of water or diet, and with its supply increases for 18 days the survival period, however the added of plant extracts in the diets decreases significantly the survival, being the highest mortality obtained in the diets increased with extracts of M. pubescens.